A preliminary study of linear accelerator-based spatially fractionated radiotherapy - Young Kyu Lee; Yunji Seol; Byeong Jin Kim; Kyu Hye Choi; Ji Hyun Hong; Chan-beom Park; Sun Hwa Kim; Hyeong Wook Park; Wonjoong Cheon; Young Nam Kang; Byung‑Ock Choi (Frontiers in Oncology)
PurposeThis study aimed to provide quantitative information for implementing Lattice radiotherapy (LRT) using a medical linear accelerator equipped with the Millennium 120 multi-leaf collimator (MLC). The research systematically evaluated the impact of varying vertex diameters and separations on dose distribution, peak-to-valley dose ratio (PVDR), and normal tissue dose.MethodsA cylindrical Virtual Water™ phantom was used to create LRT treatments using the Eclipse version 16.0 treatment planning system (Varian, Palo Alto, USA). The plans were optimized employing a 3 × 3 × 3 lattice structure with vertex diameters ranging from 0.5 to 2.0 cm and separations from 1.0 to 5.0 cm. The prescribed dose was 20.0 Gy to 50% of the vertex volume in a single fraction. Peak-to-valley dose ratio (PVDR) was calculated along three orthogonal axes, and normal tissue dose and monitor units (MU) were analyzed. Additionally, the modulation complexity score (MCS) was calculated for each plan to quantitatively assess treatment plan complexity.ResultsThe PVDR analysis demonstrated heterogeneous dose distribution, with optimal values below 30% in all directions for 5.0 cm separation. PVDR in the superior-inferior direction was consistently lower than in other directions. Normal tissue dose analysis revealed increasing mean dose with larger diameters and separations, while the volume receiving high doses decreased. MU analysis showed significant contributions from collimator angles of 315.0° and 45.0°. MCS values ranged from 0.02 to 0.17 for 0.5 cm vertex diameter and 0.08 to 0.20 for larger diameters (1.0-2.0 cm) across different separations, respectively.ConclusionsThis study demonstrates the technical feasibility of implementing LRT using a medical linear accelerator with Millennium 120 MLC. The findings provide insights into optimizing LRT treatment plans, offering a comprehensive quantitative reference for achieving desired dose heterogeneity while maintaining normal tissue protection.